Assessment of Class 10 Students' Familiarity with Badminton at SMA PGRI 4 Palembang for the 2023/2024 Academic Year - Muhammad Khofif Riyanto; Muhsana El Cintami Lanos; Widya Handayani; Hikmah Lestari (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2024)
Objective. During the 2023/2024 academic year, this research aims to evaluate the extent of badminton expertise among 10th-grade students at SMA PGRI 4 Palembang. Materials and methods. This study employs a quantitative descriptive research design, utilizing a survey methodology. The data-gathering method involved the utilization of a closed questionnaire as the instrument. The participants in the study were 60 students from SMA PGRI 4 Palembang, all of them were in the 10th grade. The data analysis was conducted using percentage-based descriptive statistics. Results. According to the research findings, the knowledge level of class 10 students at SMA PGRI 4 Palembang for the 2023/2024 academic year in the game of badminton is primarily categorized as medium, with 33.4% (20 students) falling into this category. Students in the very high category make up 23.4% (14 students), while those in the high category account for 18.4% (11 students). The very low category consists of 18.4% (11 students), and the low category comprises 6.7% (4 students). Conclusion. The findings suggest that the level of familiarity among class 10 students at SMA PGRI 4 Palembang for the 2023/2024 academic year about the game of badminton falls within the moderate range.